Calcium for Florida Turfgrasses - Travis W. Shaddox (EDIS)
Calcium is the dominant cation in all soils of agronomic importance. This 3-page document will explain the function of Calcium in turfgrasses, describe situations where applications would or would not be of value in turfgrass management, and identify calcium sources. Written by T. W. Shaddox and published by the UF/IFAS Environmental Horticulture Department, March 2018. http://edis.ifas.ufl.edu/ep554